KINERJA KEUANGAN, MANAJEMEN LABA, DAN PENGHINDARAN PAJAK: APAKAH CSR INDUSTRI KONTROVERSIAL MEMILIKI PERAN? - Ama Febriyanti; Triadi Agung Sudarto (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study examines the effect of financial performance and earnings management on corporate tax avoidance, and analyzes whether there is a moderating effect of CSR in these relationships. This research data was collected from 91 financial statements and sustainability reports of controversial companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2020 period which were selected by purposive sampling method. CSR data is encoded with content analysis, while research hypotheses are tested with moderate regression analysis. The study found that financial performance negatively affected corporate tax avoidance, while profit management showed no significant effect. In addition, it is also known that CSR does not moderate the effect of financial performance or earnings management on tax avoidance. The results of this study can be used as input for companies to consider improving financial performance in reducing the need for tax avoidance strategies, so that company legitimacy can be maintained. In addition, tax authorities can make tax-intensive related policies to boost financial performance and reduce the level of corporate tax avoidance.